Multinational companies, backward linkages and labour demand elasticities - Holger Görg; Michael E. McHenry; Eric Strobl; Frank A. Walsh (University College Dublin, UCD School of Economics, 2006)
This paper investigates the link between nationality of ownership and wage elasticities of labour demand at the level of the plant. In particular, we examine whether labour demand in multinationals becomes less elastic with respect to the wage if the plant has backward linkages with the local economy. Our empirical evidence, based on a rich plant level dataset, shows that the extent of local linkages indeed reduces the wage elasticity of labour demand. This result is economically important and holds for a number of different specifications.
hdl:10197/181
Keywords: L23; J23; F23; 330; Labour demand; Elasticities; Linkages; Multinational companies